Distinct Types of Cell Death and the Implication in Diabetic Cardiomyopathy - Chen, Yun; Hua, Yuyun; Li, Xinshuai; Arslan, Ishfaq Muhammad; Zhang, Wei; Meng, Guoliang (Frontiers in Pharmacology, 2020)
Diabetic cardiomyopathy (DCM) is a chronic complication of diabetes mellitus, characterized by abnormalities of myocardial structure and function. The researches on the models of type 1 and type 2 diabetes mellitus, as well as the application of genetic engineering technology help to understand the molecular mechanism of DCM. DCM has multiple hallmarks, including hyperglycemia, insulin resistance, increased free radical production, lipid peroxidation, mitochondrial dysfunction, endothelial dysfunction and cell death. Essentially, cell death is considered to be the terminal pathway of cardiomyocytes during DCM. Morphologically, cell death can be classified into four different forms: apoptosis, autophagy, necrosis and entosis. Apoptosis, as type I cell death, is the fastest form of cell death and mainly occurs depending on the caspase proteolytic cascade. Autophagy, as type II cell death, is a degradation process to remove damaged proteins, dysfunctional organelles and commences by the formation of autophagosome. Necrosis is type III cell death, which contains a great diversity of cell death processes, such as necroptosis and pyroptosis. Entosis is type IV cell death, displaying “cell-in-cell” cytological features and requires the engulfing cells to execute. There are also some other types of cell death such as ferroptosis, parthanatos, netotic cell death, lysosomal dependent cell death, alkaliptosis or oxeiptosis, which are possibly involved in DCM. Drugs or compounds targeting the signals involved in cell death have been used in clinic or experiment to treat DCM. This review briefly summarizes mechanisms and implications of cell death in DCM, which is beneficial to improve the understanding of cell death in DCM and may propose novel and ideal strategies in future.